2023
DOI: 10.3390/polym15183670
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Dental Cement Bond Strength with Autofocus-Laser-Cutter-Generated Grooves on Polyetheretherketone Surfaces

Tzu-Yu Peng,
Tien-Li Ma,
I-Ta Lee
et al.

Abstract: Polyetheretherketone (PEEK) is widely used in dentistry owing to its exceptional properties, including its natural appearance; however, existing surface treatment methods for bonding PEEK have limitations. Autofocus laser cutters, known for their precise engraving and cutting capabilities, offer potential for surface treatment of PEEK; thus, the objective of this study was to investigate the creation of laser groove structures on PEEK to enhance its bonding capability with dental resin cement. A dental compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Nagi et al found that in comparison with lithium disilicate restorations, PEEK endocrowns had a better internal fit and marginal gap [70]. Frameworks made of PEEK with Titanium bases had better vertical and passive fit than the Titanium frameworks [71]. Considering the stress distribution around implants, crowns made of PEEK have a similar effect to Zirconia ones [72].…”
Section: Peekmentioning
confidence: 99%
“…Nagi et al found that in comparison with lithium disilicate restorations, PEEK endocrowns had a better internal fit and marginal gap [70]. Frameworks made of PEEK with Titanium bases had better vertical and passive fit than the Titanium frameworks [71]. Considering the stress distribution around implants, crowns made of PEEK have a similar effect to Zirconia ones [72].…”
Section: Peekmentioning
confidence: 99%